Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Dengan Kompensasi Sebagai Variabel Moderasi Pada Hotel Marcopolo Bandar Lampung - Manaf, Fahri Riandi; Saputra, Febrian Eko; Candra, Ade (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of work discipline on employee performance with compensation as a moderating variable at Marcopolo Hotel, Bandar Lampung. Using a quantitative approach, data were collected via questionnaires and analyzed with SmartPLS 4. Results show that work discipline positively and significantly affects both compensation and employee performance, while compensation also significantly influences performance. Furthermore, compensation strengthens the relationship between work discipline and performance. An R-Square value of 0.510 indicates that work discipline and compensation together explain 51% of the variance in employee performance.